Environmental emission of multiresistant Escherichia coli carrying the colistin resistance gene mcr-1 from German swine farms. (25th January 2017) - Guenther, Sebastian; Falgenhauer, Linda; Semmler, Torsten; Imirzalioglu, Can; Chakraborty, Trinad; Roesler, Uwe; Roschanski, Nicole
Abstract : Objectives: Pigs have been the focus of the worldwide spread of colistin resistance. However, there is little information on the transmission of mcr-1 -containing bacteria into the environment of pig farms. We therefore rescreened environmental Escherichia coli isolates from the surrounding farm areas of three previously mcr-1 -positive swine herds in Germany. Methods: Thirty-five mixed bacterial cultures obtained from boot swabs, flies, dog faeces and manure from three pig farms in Germany in 2011–12 were non-selectively recultivated and the presence of the mcr-1 gene was checked by real-time PCR. After separation, single E. coli colonies were subsequently isolated and the presence of mcr-1 was confirmed by PCR and sequencing. In addition, phenotypic antimicrobial resistance screening and WGS followed by phylogenetic analysis and resistance genotyping as well as plasmid typing were performed. Results: Seven mcr-1 -positive E. coli strains originating from environmental boot swabs, dog faeces, stable flies and manure were found. The isolates belonged to five different STs (ST10, ST1011, ST1140, ST5281 and ST342) and harboured extensive additional resistance genes. Comparative plasmid analysis predominantly located mcr-1 on IncX4 plasmids, which are strongly related to a recently described plasmid of human clinical origin (pICBEC72Hmcr). Conclusions: WGS-based analysis of the environmental E. coli isolates of farm surroundings showed clear links to mcr-1 -harbouring E. coli recovered from pig production in Europe as well as from human clinical isolates worldwide, presenting another piece of the puzzle, which further complicates the rapidly evolving epidemiology of plasmid-mediated colistin-resistant E. coli strains.